2000
DOI: 10.1097/00007890-200006150-00030
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Intimal Thickening at Implantation as a Risk Factor for the Outcome of Cadaveric Renal Allografts1

Abstract: Fibrous intimal thickening at implantation is a determinant risk factor for the functional and morphologic outcome of cadaveric renal allografts at 1 1/2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…Recently, we have observed in 3-month protocol biopsies, that the presence of CAN associated with transplant vasculopathy (cv-score Ն1), implies a poorer allograft survival than CAN without vessel involvement (10). Data obtained from the study of donor biopsies further sustain the notion that vessel narrowing is a major determinant of outcome (11,12). Taken together, these observations suggested that the presence of chronic renal damage in protocol biopsies associated or not with chronic vascular damage, could be considered a primary efficacy variable in a hypothetical trial aimed to prevent CAN.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Recently, we have observed in 3-month protocol biopsies, that the presence of CAN associated with transplant vasculopathy (cv-score Ն1), implies a poorer allograft survival than CAN without vessel involvement (10). Data obtained from the study of donor biopsies further sustain the notion that vessel narrowing is a major determinant of outcome (11,12). Taken together, these observations suggested that the presence of chronic renal damage in protocol biopsies associated or not with chronic vascular damage, could be considered a primary efficacy variable in a hypothetical trial aimed to prevent CAN.…”
Section: Introductionmentioning
confidence: 56%
“…Recently, it has been documented in 4-month protocol biopsies that CAN associated with transplant vasculopathy implies a poorer prognosis than CAN without vessel narrowing (10). Furthermore, an association between pre-existing chronic vascular damage in the donor and decreased renal allograft survival has been described (11,12). These observations point out the importance of renal transplant vasculopathy as a major predictor of outcome and raise the question whether protocol biopsies could be employed to monitor the appearance and progression of transplant vasculopathy in the kidney in a similar way to how intracoronary ultrasounds have been employed in the heart (25).…”
Section: Discussionmentioning
confidence: 99%
“…The use of marginal donors is usually met with skepticism and subject to generalization and inappropriate The negative impact of donor vasculopathy has been stressed in some studies (17)(18)(19)(20)(21)(22)(23)(24) although questioned by others (25). …”
Section: Discussionmentioning
confidence: 99%
“…Nyberg Another approach to identifying high-risk kidneys is to use a pre-implantation biopsy in order to characterize potential kidney grafts (8), help predict the graft outcome (9,10), and provide a reference point for analysis of subsequent biopsies (8,11). The percentage of sclerotic glomeruli (9,12) and the degree of tubulointerstitial (12,13) and chronic vascular lesions (10,(14)(15)(16)(17)(18)(19) Neither clinical donor risk score (Nyberg or Pessione) showed an association with a low eGFR at 1 year (Table 2).…”
Section: The Continuing Shortage Of Organ Donors Has Led To Increasinmentioning
confidence: 99%